ANALISIS PENGELOLAAN DANA TERHADAP LIKUIDITAS BANK DI INDONESIA - Dian Ariani (universitas teuku umar, 2018)
ABSTRACT This study analyzes bank liquidity, both precautionary and involuntary liquidity. This study uses dynamic panel estimation on individual bank data covering 2002 to 2011. The results show that preventive liquidity is more determined by the operation of the bank. On the other hand, involuntary liquidity is more influenced by the condition of the financial system. Regarding size, the effect of financial and macroeconomic system conditions is greater for small banks. In addition, monetary policy in the form of minimum reserve requirements affects precautionary liquidity from small banks; while the central bank's interest rates have less influence on bank liquidity. Keywords: bank liquidity, monetary policy, financial system